Method for manufacturing toner for electrostatic charge image development

The method of manufacturing toners by melt kneading, pulverizing with inorganic fine particles, and classifying addresses the durability and flowability issues in low temperature and low humidity environments, resulting in improved toner performance and reduced image defects.

JP2025063397APending Publication Date: 2025-04-16KAO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023172540
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

The blending of large amounts of crystalline components into toners to improve low-temperature fixing leads to reduced durability, especially in low temperature and low humidity environments, resulting in decreased toner flowability and increased image scuffing and fog.

Method used

A method for manufacturing toners that involves melt kneading amorphous resin and crystalline components, followed by crushing and further pulverization in the presence of inorganic fine particles, and then classifying the product to achieve specific temperature, heat-absorbing, and bulk density properties.

Benefits of technology

The method produces toners with enhanced durability, flowability, and bulk density, effectively suppressing image scuffing and fog even in continuous printing under low temperature and low humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063397000001
    Figure 2025063397000001
  • Figure 2025063397000002
    Figure 2025063397000002
  • Figure 2025063397000003
    Figure 2025063397000003
Patent Text Reader

Abstract

To provide a method for manufacturing a toner for electrostatic charge image development which suppresses blurring and fogging of a solid image, even in continuous printing under a low temperature and low humidity environment.SOLUTION: A method for manufacturing a toner for electrostatic charge image development includes a step (1) of melting and kneading at least an amorphous resin and a crystalline component, a step (2) of pulverizing the kneaded product obtained in the step (1), and then further pulverizing the obtained pulverized product in the presence of inorganic fine particles, and a step (3) of classifying the crushed product obtained in the step (2), wherein the toner has an endothermic peak temperature derived from the crystalline component by a differential scanning calorimeter of 60°C or higher and 90°C or lower, the endothermic quantity of the endothermic peak is 4.0 J / g or more and 20.0 J / g or less, and the bulk density by powder rheometer measurement of the toner is 0.570 g / mL or more and 0.610 g / mL or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a toner for developing electrostatic images used in developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like. [Background technology]

[0002] With the development of electrophotographic systems, there is a demand for the development of toners for developing electrostatic images (hereinafter, simply referred to as "toners") that can handle higher image quality and faster speeds. For example, as the machine speed increases, the amount of heat applied to the toner applied to the recording paper during fixing decreases, so toners are required to have better low-temperature fixing properties.

[0003] Although the toner mainly contains an amorphous resin as a main component, the incorporation of a crystalline component, which is effective in improving low-temperature fixing properties, is being considered.

[0004] On the other hand, in order to increase the efficiency of toner transport and replenishment within an image forming apparatus, adjustment of the bulk density and loose apparent density of toner has been proposed (see Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-124317 A [Patent Document 2] JP 2014-89384 A [Patent Document 3] International Publication No. 2018-061933 [Patent Document 4] JP 2016-170246 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, when a large amount of crystalline components is blended in a toner to improve low-temperature fixability, the crystalline components are easily exposed on the surface of the toner particles, and durability is reduced. In particular, in a low-temperature and low-humidity environment, the fluidity of the toner deteriorates due to the detachment of external additives, which causes blurring of solid images and fogging due to high charging.

[0007] The present invention relates to a method for producing a toner for developing electrostatic images, which suppresses blurring and fogging of solid images even during continuous printing in a low-temperature, low-humidity environment. [Means for solving the problem]

[0008] The present invention relates to a method for producing a toner for developing electrostatic images, the method comprising the steps of: (1) melt-kneading at least an amorphous resin and a crystalline component; (2) pulverizing the kneaded product obtained in the step (1) and then further pulverizing the pulverized product obtained in the step (2) in the presence of inorganic fine particles; and (3) classifying the pulverized product obtained in the step (2), wherein the toner has an endothermic peak temperature derived from the crystalline component as measured by a differential scanning calorimeter of 60° C. or more and 90° C. or less, an endothermic amount of the endothermic peak of 4.0 J / g or more and 20.0 J / g or less, and the toner has a bulk density as measured by a powder rheometer of 0.570 g / mL or more and 0.610 g / mL or less. Effect of the Invention

[0009] According to the method of the present invention, a toner for developing electrostatic images can be obtained which suppresses blurring and fogging of solid images even during continuous printing in a low-temperature, low-humidity environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention is a method for producing a toner containing a large amount of crystalline components by a melt-kneading and pulverizing method, in which the kneaded product is coarsely pulverized, and then the coarsely pulverized product is finely pulverized in the presence of inorganic fine particles, thereby obtaining a toner for developing electrostatic images. The reason why the method of the present invention can obtain a toner having excellent durability even in a low-temperature and low-humidity environment is not clear, but is presumed to be as follows. Note that the following mechanism is presumed and is not limited thereto.

[0011] In the present invention, the fine pulverization is carried out in the presence of inorganic fine particles, so that the inorganic fine particles can be strongly and uniformly attached to the toner particles, and the resulting toner has high fluidity and high bulk density. As a result, the toner layer thickness becomes uniform when the toner layer is formed on the developing roller, and the occurrence of blurred images can be suppressed. In addition, the high bulk density makes it easier to form a dense conductive path structure in the toner layer, and allows charge to leak more efficiently, so that excessive charging of the toner can be significantly suppressed in a low-temperature, low-humidity environment, and the occurrence of fogging can be suppressed.

[0012] The method for producing the toner of the present invention includes the following steps (1), (2), and (3).

[0013] The step (1) is a step of melt-kneading at least an amorphous resin and a crystalline component.

[0014] Examples of the amorphous resin include amorphous polyester resin, vinyl resin such as styrene acrylic resin, amorphous epoxy resin, amorphous polycarbonate, amorphous polyurethane, and composite resin containing two or more of these resins. Among these, amorphous polyester resin is preferred from the viewpoint of low-temperature fixability.

[0015] As the amorphous polyester resin, a polycondensation product of an alcohol component containing an alkylene oxide adduct of bisphenol A and a carboxylic acid component containing an aromatic dicarboxylic acid compound is preferable.

[0016] Examples of the alkylene oxide adduct of bisphenol A include those represented by the formula (I):

[0017] [ka]

[0018] (In the formula, OR and RO are oxyalkylene groups, R is an ethylene group and / or a propylene group, x and y are the average number of moles of alkylene oxide added, each of which is a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less.) Preferred is a compound represented by the following formula:

[0019] From the viewpoint of low-temperature fixing ability, the content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 100 mol %.

[0020] Examples of other alcohol components include aliphatic diols, bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, trimethylolpropane and other trihydric or higher alcohols.

[0021] Examples of the aromatic dicarboxylic acid compound include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0022] The content of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 50 mol % or more, more preferably 60 mol % or more, even more preferably 70 mol % or more, and is preferably 98 mol % or less, more preferably 90 mol % or less.

[0023] Examples of other carboxylic acid components include fumaric acid, maleic acid, succinic acid, succinic acid derivatives substituted with a hydrocarbon group, aliphatic dicarboxylic acids such as glutaric acid, adipic acid, and sebacic acid, trivalent or higher carboxylic acids such as trimellitic acid and pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0024] The alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.

[0025] In this specification, macromonomers and hydroxycarboxylic acids are not included in the alcohol component and the carboxylic acid component.

[0026] From the viewpoint of adjusting the softening point of the polyester resin, the equivalent ratio of the carboxy group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0027] The amorphous polyester resin can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and further, if necessary, in the presence of an esterification promoter, a polymerization inhibitor, etc., at a temperature of preferably 160°C or higher, more preferably 200°C or higher, and preferably 250°C or lower, more preferably 240°C or lower.

[0028] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropoxybis(triethanolaminate). The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the esterification promoter include gallic acid. The amount of the esterification promoter used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the polymerization inhibitor include tert-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.

[0029] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.

[0030] The crystallinity of a resin is represented by a crystallinity index defined as the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, that is, the value of [softening point / maximum endothermic peak temperature]. An amorphous resin is a resin in which no endothermic peak is observed, or if an endothermic peak is observed, the resin has a crystallinity index of more than 1.4, preferably more than 1.5, more preferably 1.6 or more, or less than 0.6, preferably 0.5 or less. On the other hand, the crystallinity index of the crystalline resin is 0.6 or more, preferably 0.7 or more, more preferably 0.9 or more, and is 1.4 or less, preferably 1.2 or less, more preferably 1.1 or less. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. In the case of a crystalline resin, the maximum endothermic peak temperature is the melting point.

[0031] From the viewpoint of charging stability, the softening point of the amorphous resin is preferably 70° C. or higher, more preferably 90° C. or higher, and even more preferably 100° C. or higher, and from the viewpoint of low-temperature fixing property, it is preferably 170° C. or lower, more preferably 160° C. or lower, and even more preferably 150° C. or lower.

[0032] The glass transition temperature of the amorphous resin is preferably 40° C. or higher, more preferably 50° C. or higher, from the viewpoint of charging stability, and is preferably 80° C. or lower, more preferably 70° C. or lower, from the viewpoint of low-temperature fixability.

[0033] The content of the amorphous resin in the toner is preferably 60% by mass or more, more preferably 65% ​​by mass or more, even more preferably 70% by mass or more, and preferably 95% by mass or less, more preferably 93% by mass or less, even more preferably 90% by mass or less.

[0034] Examples of the crystalline component include crystalline polyester resin, wax, crystalline polyurethane, etc., which may be used alone or in combination of two or more. In the present invention, from the viewpoint of dispersibility in the toner, crystalline polyester resin or wax is preferred.

[0035] As the crystalline polyester resin, a polycondensation product of an alcohol component containing an aliphatic diol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound is preferable.

[0036] Examples of the aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol. Of these, ethylene glycol is preferred from the viewpoint of low-temperature fixability.

[0037] The aliphatic diol has 2 or more carbon atoms, and from the viewpoint of low-temperature fixability, it has preferably 14 or less, more preferably 8 or less, and further preferably 4 or less.

[0038] The content of the aliphatic diol in the alcohol component is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and still more preferably 95 mol% or more, and 100 mol% or less. When the alcohol component contains a monoalcohol, it is preferably 98 mol% or less, more preferably 95 mol% or less.

[0039] Examples of other alcohol components include alkylene oxide adducts of bisphenol A, aromatic diols such as bisphenol A, hydrogenated bisphenol A, trihydric or higher alcohols such as sorbitol, pentaerythritol, glycerin, and trimethylolpropane.

[0040] Examples of the aliphatic dicarboxylic acid compound include succinic acid (carbon number: 4), fumaric acid (carbon number: 4), adipic acid (carbon number: 6), suberic acid (carbon number: 8), azelaic acid (carbon number: 9), sebacic acid (carbon number: 10), dodecanedioic acid (carbon number: 12), tetradecanedioic acid (carbon number: 14), anhydrides of these acids, and alkyl esters of these acids having a carbon number of 1 to 3. Here, when the aliphatic dicarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.

[0041] From the viewpoint of hydrophobicity, the carbon number of the aliphatic dicarboxylic acid compound is preferably 4 or more, more preferably 8 or more, even more preferably 10 or more, and still more preferably 12 or more, and from the viewpoint of low-temperature fixability, the carbon number is preferably 16 or less, more preferably 14 or less.

[0042] The content of the aliphatic dicarboxylic acid compound in the carboxylic acid component is preferably 80 mol % or more, more preferably 85 mol % or more, and 100 mol % or less. When the carboxylic acid component contains a monocarboxylic acid compound, the content is preferably 98 mol % or less, more preferably 95 mol % or less.

[0043] Examples of other carboxylic acid components include aromatic dicarboxylic acid compounds such as phthalic acid, isophthalic acid, and terephthalic acid, and trivalent or higher carboxylic acid compounds such as trimellitic acid and pyromellitic acid.

[0044] Furthermore, from the viewpoint of improving hydrophobicity, the alcohol component and / or the carboxylic acid component of the crystalline polyester resin preferably contains a monofunctional monomer.

[0045] From the viewpoint of improving hydrophobicity, the monofunctional monomer preferably contains an aliphatic monocarboxylic acid compound and / or an aliphatic monoalcohol.

[0046] Examples of monofunctional monomers contained in the alcohol component include aliphatic monoalcohols such as capryl alcohol, capric alcohol, lauryl alcohol, myristyl alcohol, palmityl alcohol, stearyl alcohol, and behenyl alcohol.

[0047] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monoalcohol is preferably 6 or more, more preferably 9 or more, even more preferably 10 or more, and even more preferably 12 or more, and from the viewpoint of low-temperature fixability, the carbon number is preferably 24 or less, more preferably 23 or less, and even more preferably 22 or less.

[0048] Examples of monofunctional monomers contained in the carboxylic acid component include aliphatic monocarboxylic acids such as caproic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid, and aliphatic monocarboxylic acid compounds such as alkyl esters of these acids in which the alkyl group has 1 to 3 carbon atoms.

[0049] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monocarboxylic acid compound is preferably 6 or more, more preferably 9 or more, and even more preferably 10 or more, and from the viewpoint of low-temperature fixability, it is preferably 24 or less, more preferably 23 or less, and even more preferably 22 or less. Here, when the aliphatic monocarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.

[0050] The content of the monofunctional monomer in the total amount of the alcohol component and the carboxylic acid component is preferably 2 mol % or more, more preferably 3 mol % or more, even more preferably 5 mol % or more, and is preferably 30 mol % or less, more preferably 25 mol % or less, even more preferably 20 mol % or less.

[0051] The equivalent ratio of the carboxy group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.8 or more, more preferably 0.9 or more, from the viewpoint of adjusting the softening point of the polyester resin, and is preferably 1.2 or less, more preferably 1.1 or less, from the viewpoint of low-temperature fixability.

[0052] The polycondensation reaction conditions of the alcohol component and the carboxylic acid component of the crystalline polyester resin are similar to those of the amorphous polyester resin, except that the suitable reaction temperature is 120°C or higher, more preferably 180°C or higher, and 230°C or lower, more preferably 220°C or lower.

[0053] From the viewpoint of storage stability, the softening point of the crystalline polyester resin is preferably 50° C. or higher, more preferably 65° C. or higher, and even more preferably 70° C. or higher, and from the viewpoint of low-temperature fixability, it is preferably 120° C. or lower, and more preferably 100° C. or lower.

[0054] The wax may be any wax used as a toner release agent, such as polypropylene wax, polyethylene wax, ethylene propylene copolymer wax, aliphatic hydrocarbon waxes such as microcrystalline wax, paraffin wax, Fischer-Tropsch wax, or oxides thereof, ester waxes such as carnauba wax, montan wax, or deacidified waxes thereof, or fatty acid ester wax, fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts, all of which have crystallinity.

[0055] The melting point of the crystalline component is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of durability, and is preferably 90° C. or lower, more preferably 85° C. or lower, from the viewpoint of low-temperature fixability.

[0056] The amount of the crystalline component used in step (1) is preferably 4 parts by mass or more, more preferably 6 parts by mass or more, and preferably 40 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the amorphous resin.

[0057] In step (1), examples of raw materials that can be subjected to melt kneading together with the amorphous resin and the crystalline component include additives such as colorants, charge control agents, magnetic powders, flowability improvers, conductivity adjusters, reinforcing fillers such as fibrous substances, antioxidants, and cleaning improvers.

[0058] As the colorant, dyes, pigments, magnetic materials, etc. used as colorants for toners can be used. For example, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazo yellow, etc. can be mentioned. In the present invention, the toner may be either a black toner or a color toner.

[0059] From the viewpoint of improving the image density and low-temperature fixability of the toner, the content of the colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0060] The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.

[0061] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", "Bontron N-11", and "Bontron N-79" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes having a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Kasei Corporation); and styrene-acrylic resins, such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Kasei Co., Ltd.).

[0062] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizenspiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (all manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE NX VP434 (Clariant), nitroimidazole derivatives, and organometallic compounds.

[0063] From the viewpoint of the charging stability of the toner, the content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0064] In step (1), the raw materials to be melt-kneaded are preferably premixed using a Henschel mixer or the like and then subjected to the melt-kneading step. The raw materials can be melt-kneaded in a conventional manner using a known kneader such as an internal kneader, a single-screw or twin-screw extruder, or an open roll-type kneader.

[0065] After step (1), the kneaded mixture is appropriately cooled until it reaches a pulverizable hardness, and then is subjected to the subsequent step (2). Here, cooling refers to cooling the kneaded mixture to 0°C to 50°C, or to a temperature equal to or lower than the glass transition temperature of the binder resin in the kneaded mixture.

[0066] In step (2), the kneaded product obtained in step (1) is pulverized, and the pulverized product obtained is then pulverized in the presence of inorganic fine particles. Hereinafter, the pulverization in the first stage is also called "coarse pulverization," and the pulverization in the second stage, which is performed in the presence of inorganic fine particles, is also called "fine pulverization."

[0067] Examples of the crushing machine used for the coarse crushing include a hammer mill, an atomizer, and a rotoplex.

[0068] In the coarse pulverization, it is preferable to coarsely pulverize the kneaded product obtained in step (1) until the particle size becomes about 0.1 to 3 mm, and then pass the product through a sieve with a mesh size of about 2 to 3 mm, and provide the pulverized product that passed through the sieve as pulverized product with a maximum diameter of 2 to 3 mm or less to fine pulverization.

[0069] Examples of inorganic fine particles used in the fine pulverization include silicon dioxide (silica), titanium dioxide, aluminum oxide, zinc oxide, magnesium oxide, cerium oxide, iron oxide, copper oxide, tin oxide, etc. Among these, from the viewpoint of imparting electrostatic charge, silica or titanium dioxide is preferred, silica is more preferred, and hydrophobic silica that has been subjected to a hydrophobic treatment is even more preferred. These can be used alone or in combination of two or more kinds.

[0070] Examples of hydrophobic treatment agents for hydrophobizing the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.

[0071] The inorganic fine particles have an average particle size of preferably 5 nm or more, more preferably 7 nm or more, and preferably 40 nm or less, more preferably 20 nm or less, from the viewpoints of the chargeability, fluidity and durability of the toner.

[0072] The amount of inorganic fine particles used in step (2) is, from the viewpoint of the chargeability, fluidity and durability of the toner, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 0.8 parts by mass or more, and is preferably 2.8 parts by mass or less, more preferably 2.0 parts by mass or less, and more preferably 1.5 parts by mass or less, per 100 parts by mass of the coarsely ground material.

[0073] It is preferable that the inorganic fine particles are mixed in advance with the coarsely pulverized material using a mixer such as a Henschel mixer, and then the mixture is finely pulverized.

[0074] Examples of the pulverizer used for fine pulverization include a fluidized bed counter jet mill, an impact plate jet mill, and a rotary mechanical mill.

[0075] The degree of fine pulverization is preferably adjusted appropriately depending on the target toner particle size, but it is preferable to appropriately pulverize the coarsely pulverized product until the volume median particle size is about 5.0 to 10.0 μm, and then use the pulverized product in step (3).

[0076] Step (3) is a step of classifying the pulverized product (finely pulverized product) obtained in step (2).

[0077] Examples of classifiers used for classification include air flow classifiers, inertial classifiers, and sieve classifiers.

[0078] In the present invention, it is preferable to further carry out a step (4) of mixing the classified product obtained in the step (3) with an external additive, from the viewpoint of improving transferability.

[0079] Examples of the external additive include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as melamine resin fine particles and polytetrafluoroethylene resin fine particles, and two or more of them may be used in combination. Among these, silica is preferred, and from the viewpoint of the transferability of the toner, hydrophobic silica that has been subjected to a hydrophobic treatment is more preferred.

[0080] Examples of hydrophobic treatment agents for hydrophobizing the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.

[0081] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the average particle size of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.

[0082] The external addition treatment by mixing the toner particles with the external additives can be carried out according to a conventional method, and a mixer such as a Henschel mixer can be used.

[0083] From the viewpoints of the chargeability, fluidity, and transferability of the toner, the amount of the external additive used is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner particles (classified product) before treatment with the external additive, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.

[0084] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50 ) refers to the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size. In addition, when the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is regarded as the volume median particle size of the toner.

[0085] The toner obtained by the method of the present invention contains a large amount of crystalline components, and as an indicator thereof, the endothermic peak temperature derived from the crystalline components measured by a differential scanning calorimeter is 60°C or more and 90°C or less, and the endothermic amount of the endothermic peak is 4.0 J / g or more and 20.0 J / g or less.

[0086] The endothermic peak temperature of the toner derived from the crystalline component as measured by a differential scanning calorimeter is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of durability, and is preferably 90° C. or lower, more preferably 85° C. or lower, from the viewpoint of low-temperature fixability.

[0087] The endothermic amount of the endothermic peak derived from the crystalline component is preferably 4.1 J / g or more, more preferably 4.2 J / g or more, from the viewpoint of suppressing excessive charging, and is preferably 17.0 J / g or less, more preferably 15.0 J / g or less, even more preferably 10.0 J / g or less, and even more preferably 7.0 J / g or less, from the viewpoint of durability.

[0088] The toner obtained by the method of the present invention is characterized by a high bulk density because the inorganic fine particles are strongly and uniformly attached as described above. Therefore, the bulk density of the toner measured by a powder rheometer is 0.570 g / mL or more, preferably 0.575 g / mL or more, more preferably 0.580 g / mL or more, and 0.610 g / mL or less, preferably 0.600 g / mL or less, more preferably 0.590 g / mL or less.

[0089] The toner obtained by the method of the present invention can be used as a toner for one-component development, or mixed with a carrier to form a two-component developer. EXAMPLES

[0090] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like were measured by the following methods.

[0091] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The amount of plunger descent of the flow tester is plotted against the temperature, and the temperature at which half of the sample has flowed out is taken as the softening point.

[0092] [Maximum endothermic peak temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan, Inc.), weigh 0.01 to 0.02 g of sample into an aluminum pan, cool from room temperature (25°C) to 0°C at a rate of 10°C / min, and maintain at 0°C for 1 minute. Then, measure at a rate of 10°C / min. The temperature of the peak with the largest peak area among the observed endothermic peaks is regarded as the maximum endothermic peak temperature.

[0093] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and cooled to 0°C at a rate of 10°C / min. The sample is then heated to 150°C at a rate of 10°C / min, and the endothermic peak is measured. The glass transition temperature is the temperature at the intersection of the extension of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak.

[0094] [Melting point of crystalline component] (1) Crystalline resin The maximum endothermic peak temperature of the resin is defined as the melting point. (2) Crystalline components other than crystalline resins Using a differential scanning calorimeter "DSC Q20" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C at a heating rate of 10°C / min, and cooled to -10°C at a heating rate of 5°C / min. The sample is then heated to 180°C at a heating rate of 10°C / min and measured. The maximum endothermic peak temperature observed in the melting endothermic curve obtained is taken as the melting point.

[0095] [Average particle size of inorganic fine particles and external additives used in fine grinding] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average of major and minor diameters) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these by number.

[0096] [Volume median particle size of toner (D 50 )〕 Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" (manufactured by Kao Corporation, HLB (Griffin) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured, and the volume median particle size (D 50 ) is required.

[0097] [Toner endothermic peak temperature and endothermic amount of the endothermic peak] Using a differential scanning calorimeter "DSC Q20" (manufactured by TA Instruments Japan, Inc.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C at a heating rate of 10°C / min, and cooled to -10°C at a heating rate of 5°C / min. The sample is then heated to 180°C at a heating rate of 10°C / min and measured. The endothermic peak temperature is calculated from the apex of the endothermic curve obtained, and the endothermic amount is calculated from the area enclosed by the baseline and the endothermic peak.

[0098] [Bulk Density of Toner] The measurement is performed using a powder flow analyzer, Powder Rheometer FT-4 (manufactured by Freeman Technology). First, a 48 mm diameter propeller-type blade dedicated to FT-4 measurement is attached to the main body of the device, and the dedicated container for FT-4 measurement (split container with a diameter of 50 mm and a volume of 160 mL) and the attached container (diameter of 50 mm and a volume of 85 mL) are connected with a dedicated jig, and approximately 100 g of toner is poured into the connected container. (a) The blade rotation speed is 60 mm / sec, and the vertical penetration speed into the powder layer is such that the angle between the path traced by the outermost edge of the moving blade and the surface of the toner layer is 5°. The blade penetrates in a clockwise direction relative to the surface of the toner layer to a position 10 mm from the bottom of the toner layer. Then, the blade is rotated at a speed of 60 mm / sec, and the blade is advanced vertically into the powder layer at an angle of 2° in a clockwise direction relative to the surface of the toner layer, until it is 1 mm from the bottom of the toner layer. Thereafter, the blade is rotated at a speed of 60 mm / sec, and the blade is moved in a clockwise direction relative to the surface of the toner layer at an angle of 5° to the extraction speed from the powder layer, to a position 100 mm from the bottom of the toner layer, and extraction is performed. Once removal is complete, the blade is rotated alternately clockwise and counterclockwise in small increments to brush off any toner adhering to the blade. (b) After carrying out the above series of steps (a) five times, in order to adjust the volume of the toner for evaluation, the toner is drained off so that only the measurement container is filled with toner, and a toner layer with the same volume as the measurement container is prepared. The mass of the obtained toner layer is divided by the volume of the measurement container to obtain the bulk density (g / mL).

[0099] Resin manufacturing example 1 The alcohol components shown in Table 1, carboxylic acid components other than trimellitic anhydride, and esterification catalyst were placed in a 5-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and the mixture was heated to 200°C under a nitrogen atmosphere and reacted for 6 hours. After further heating to 210°C, trimellitic anhydride was added and reacted for 1 hour at normal pressure (101.3 kPa), and further reacted at 40 kPa until the desired softening point was reached, to obtain an amorphous polyester resin (resin A1). The physical properties of the obtained resin are shown in Table 1.

[0100] [Table 1]

[0101] Resin manufacturing example 2 2 L of xylene was placed in a 10 L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a flow-down condenser, a dropping funnel and a nitrogen inlet tube, and 880 g of styrene, 220 g of n-butyl acrylate and 100 g of dibutyl peroxide as a radical polymerization initiator were placed in the dropping funnel. Under a nitrogen atmosphere, the xylene was heated to 135°C while stirring, and the mixture in the dropping funnel was dropped over 1 hour. After that, the temperature was raised to 200°C and held at 200°C for 2 hours, and then the pressure in the flask was further reduced and held at 8 kPa for 1 hour, and xylene was removed to obtain a styrene-acrylic resin (resin A2). The glass transition temperature of the obtained resin was 54°C and the softening point was 115°C.

[0102] Resin manufacturing example 3 The alcohol and carboxylic acid components shown in Table 2 were placed in a 5-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. An esterification catalyst was then added, and the reaction was carried out at 8.0 kPa until the softening points shown in Table 2 were reached, obtaining crystalline polyester resins (resins C1 to C4). The physical properties are shown in Table 2.

[0103] [Table 2]

[0104] Examples 1 to 12, Comparative Examples 1, 2, and 4 100 parts by mass of the amorphous resin and crystalline component shown in Table 3, 5 parts by mass of colorant "ECB-301" (manufactured by Dainichi Seikagaku Co., Ltd., phthalocyanine blue (PB15:3)), and 0.5 parts by mass of charge control agent "Bontron E-304" (manufactured by Orient Chemical Industries Co., Ltd.) were mixed for 1 minute using a Henschel mixer, and then melt-kneaded under the conditions shown below.

[0105] Co-rotating twin screw extruder "PCM-30" (Ikegai Co., Ltd., shaft diameter 2.9 cm, shaft cross-sectional area 7.06 cm 2The operating conditions were: barrel temperature 100°C, shaft rotation speed 200 r / min (shaft rotation peripheral speed 0.30 m / sec), mixture supply speed 10 kg / h (mixture supply amount per unit cross-sectional area of ​​the shaft 1.42 kg / h cm 2 ) was.

[0106] The kneaded product thus obtained was cooled to about 25°C, and then coarsely pulverized in a pulverizer "Rotoplex" (manufactured by Hosokawa Micron Corporation) and passed through a sieve with 2 mm openings to obtain a coarsely pulverized product with a maximum diameter of 2 mm or less. 100 parts by mass of the coarsely pulverized product thus obtained and 1 part by mass of inorganic fine particles shown in Table 3 were mixed in a Henschel mixer for 2 minutes to obtain a coarsely pulverized product to which hydrophobic silica was attached. The coarsely ground material with the hydrophobic silica attached was finely ground using a DS2 air classifier (impingement plate type, manufactured by Japan Pneumatic Co., Ltd.) by adjusting the grinding pressure so that the volume median particle size became 8.0 μm.

[0107] The resulting finely pulverized product was classified using a DSX2 type air classifier (manufactured by Japan Pneumatic Mfg. Co., Ltd.) by adjusting the static pressure (internal pressure) so that the volume median particle size was 8.5 μm, thereby obtaining toner particles.

[0108] 100 parts by weight of the obtained toner particles and 1 part by weight of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1 part by weight of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives were mixed in a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) at 2100 r / min (circumferential speed: 29 m / sec) for 3 minutes to obtain a toner.

[0109] Comparative Example 3 A toner was obtained in the same manner as in Example 1, except that inorganic fine particles were not used (the coarsely ground material was not mixed with the inorganic fine particles), the coarsely ground material was finely ground, and the amount of "R972" used as an external additive was changed to 2 parts by mass.

[0110] Details of the wax and inorganic fine particles used in the examples and comparative examples are as follows.

[0111] 〔wax〕 W1: HNP-9 (paraffin wax, manufactured by Nippon Seiro Co., Ltd.), melting point 77°C W2: Carnauba wax C1 (manufactured by Kato Yoko Co., Ltd.), melting point 83°C W3: WEP-8 (NOF Corp., synthetic ester wax), melting point 80°C

[0112] [Inorganic fine particles] Silica 1: Hydrophobic silica, R972 (manufactured by Nippon Aerosil Co., Ltd.), average particle size 16 nm, hydrophobic treatment agent DMDS Silica 2: Hydrophobic silica, RX300 (manufactured by Nippon Aerosil Co., Ltd.), average particle size 8 nm, hydrophobic treatment agent HMDS

[0113] Test Example 1 [Image blurring under low temperature and low humidity (LL)] The toner was mounted on a non-magnetic single-component developing device "OKI MICROLINE 5400" (manufactured by Oki Data Corporation), and an A4-sized solid black image was printed under conditions of a temperature of 10°C and a relative humidity of 20%. Next, 500 sheets were printed at a printing rate of 1%, and then another A4-sized solid black image was printed. J paper (manufactured by Fuji Xerox) was used as the printing medium. The image density (ID1) of the initial solid black image at a center portion 5 cm from the bottom and the image density (ID2) of the center portion 5 cm from the bottom after printing 500 sheets were measured using a reflection densitometer "RD-915" (manufactured by Gretag Macbeth Co., Ltd.), and the difference in image density between ID1 and ID2 was confirmed. If the difference in image density exceeded 0.4, the number of prints was used as the evaluation result of the suppression of smearing, and if it did not exceed 0.4, 500 sheets were printed at a time and evaluated in the same manner. The results are shown in Table 3. The more the number of prints, the better the suppression of smearing.

[0114] Test Example 2 [Photoconductor fogging under low temperature and low humidity (LL)] The toner was mounted on a non-magnetic one-component developing device "OKI MICROLINE 5400" (manufactured by Oki Data Corporation), and 5,000 images with a print rate of 1% were printed under the conditions of a temperature of 10°C, a relative humidity of 20%, and a 20-second break per page (after printing one page, the next page was printed after a 20-second break). Next, a solid white image (print rate of 0%) was printed, and the power was turned off during the printing. After that, the toner on the surface of the photoconductor was attached with "Scotch (registered trademark) Mending Tape 810" (manufactured by Sumitomo 3M, width: 18 mm), and the color density was measured at five equally spaced points with an image density meter "GRETAG SPM50" (manufactured by GRETAG), and the difference from the color density of the tape itself before the toner was attached was calculated, and the average of the measured values ​​was calculated. The results are shown in Table 3.

[0115] [Table 3]

[0116] From the above results, it is understood that in Examples 1 to 12, blurring of solid images and fogging of the photoreceptor are suppressed even during continuous printing in a low-temperature, low-humidity environment. In contrast, in Comparative Example 1, which has a small amount of crystalline components, the conductive path is small, so the charge cannot be sufficiently leaked, and photoreceptor fogging occurs due to excessive charging of the toner. In Comparative Example 2, in which the bulk density of the toner is too high, the toner particles are packed too densely, so image blurring occurs due to poor formation of the toner layer, while in Comparative Example 3, in which the bulk density of the toner is too low, the fluidity is too low, so the toner layer is poorly formed, and further the contact area between the toner particles is small, and the efficiency of charge leakage is poor, so both image blurring and photoreceptor fogging occur. In Comparative Example 4, which has an endothermic peak temperature of 100°C derived from the crystalline polyester resin, the crystalline polyester has high crystallinity and the electrons in the crystal lattice are fixed, so the conductivity is low and the charge is difficult to leak, and photoreceptor fogging occurs. [Industrial Applicability]

[0117] The electrostatic image developing toner obtained by the method of the present invention is suitably used for developing latent images formed in electrostatic image developing methods, electrostatic recording methods, electrostatic printing methods and the like.

Claims

1. 1. A method for producing a toner for developing electrostatic images, comprising: a step (1) of melt-kneading at least an amorphous resin and a crystalline component; a step (2) of pulverizing the kneaded product obtained in the step (1) and then further pulverizing the pulverized product obtained in the step (2) in the presence of inorganic fine particles; and a step (3) of classifying the pulverized product obtained in the step (2), wherein the toner has an endothermic peak temperature derived from the crystalline component as measured by a differential scanning calorimeter of 60° C. or more and 90° C. or less, an endothermic amount of the endothermic peak of 4.0 J / g or more and 20.0 J / g or less, and a bulk density of the toner as measured by a powder rheometer of 0.570 g / mL or more and 0.610 g / mL or less.

2. 2. The method for producing a toner for developing electrostatic images according to claim 1, wherein the amount of the crystalline component used in the step (1) is 4 parts by mass or more and 40 parts by mass or less based on 100 parts by mass of the amorphous resin.

3. 3. The method for producing a toner for developing electrostatic images according to claim 1, wherein in the step (2), 0.1 parts by mass or more and 2.8 parts by mass or less of inorganic fine particles are used for 100 parts by mass of the pulverized product.

4. 4. The method for producing a toner for developing electrostatic images according to claim 1, wherein the amorphous resin is an amorphous polyester resin.

Citation Information

Patent Citations

  • Toner, developer, toner container, process cartridge, and image forming apparatus

    JP2014089384A

  • Toner storage container, and image formation device

    JP2016170246A

  • Toner for electrostatic charge image development, two-component developer for electrostatic charge image development, and method for manufacturing toner for electrostatic charge image development

    JP2018124317A

  • Toner for electrostatic charge image development

    WO2018061933A1